Synthesis and antiviral effect of phosphamide modified vidarabine for treating HSV 1 infections. (15th November 2021) - Wang, Zhenhao; Zang, Ruochen; Niu, Zhao; Wang, Wei; Wang, Xin; Tang, Yu
Graphical abstract: Abstract: Vidarabine (ARA) was one of the earliest marine-related compounds to be used clinically for antiviral therapy, however, its fast metabolism is the main defect of this drug. To overcome this, we designed and synthesized a group of phosphamide-modified ARA compounds using ProTide technology. With a phosphamide modification, these compounds could become the substrate of specific phospholipase enzymes expressed in the liver. Among all 16 synthesized compounds, most showed stronger activity against herpes simplex virus type 1 (HSV-1) than ARA (EC50 of approximately 10 μM). The top three compounds were compound 2 (EC50 = 0.52 ± 0.04 μM), compound 6 (EC50 = 1.05 ± 0.09 μM) and compound 15 (EC50 = 1.18 ± 0.08 μM) (about 2 times higher than S p type compound 2). This study provides evidence for use of the phosphamide modification, which could give ARA higher activity and liver cell targeting.